A novel detachable head-mounted device for simultaneous EEG and photoacoustic monitoring of epilepsy in freely moving rats. (February 2015) - Wang, Bo; Zhou, Junli; Carney, Paul; Jiang, Huabei
Highlights: We integrated EEG and photoacoustic system into a small detachable device. It is the first long time hemodynamic monitoring on freely moving animals. We also performed simultaneous video recording. The photoacoustic, EEG and video data are jointly analyzed for epilepsy study. We compared results in free moving, anesthetized, and control rat experiments. Abstract: The study of neuro-hemodynamic changes in freely moving animals provides for a better understanding of brain dynamics in normal and disease states. While it has been shown that hemodynamic changes are closely related to seizures, methods for detection in freely moving animals are limited. In this work, we integrate photoacoustic sensor technology and electroencephalography into a small portable device that can be attached on the head of wake freely moving animals. We demonstrate chronic simultaneous monitoring of photoacoustic and electroencephalographic signals in an acute seizure model of epilepsy. Our results demonstrate that both the neural and vascular responses during seizures in freely moving rats have characteristics which are observed to be different and more diverse from that of anesthetized rats. This implies that the neurovascular coupling in seizure in free moving animals are more complicated, which calls for more detailed study in future. To the best of our knowledge, this is the first time for hemodynamic monitoring of seizure in free moving animals. This technology also promises for other hemodynamic related research study in freely moving small animals.